The Influence of Artificial Intelligence (AI) Use on Learning Motivation and Task Independence Among PTIK Students at Semarang State University - Pratama, Faisal Rizki Rafi; Ekarini, Fitria (Journal of Educational Sciences, 2025)
The digital revolution has brought significant changes to education, particularly through the use of Artificial Intelligence (AI). This study, titled “The Influence of Artificial Intelligence (AI) on Learning Motivation and Task Independence Among PTIK Students at Semarang State University,” aims to examine the role of AI in supporting students’ academic engagement and autonomy. The research involved 30-100 students, enrolled in the Informatics and Computer Engineering Education Program (PTIK). Learning activities generally included lectures, discussions, and project-based tasks, where students actively utilized AI applications such as ChatGPT, Grammarly, and programming assistants. The integration of these tools created a more interactive classroom atmosphere, encouraging motivation and independence in task completion. A questionnaire was designed based on three variables—AI usage, learning motivation, and task independence—validated by experts and distributed online through Google Forms. The instrument employed a five-point Likert scale, and responses were collected within two weeks. Using multiple linear regression analysis, the results revealed that AI usage had a positive and significant influence on both learning motivation and task independence. Key factors included ease of information access, real-time feedback, and personalized learning experiences. These findings highlight the strategic importance of AI-based approaches in enhancing learning effectiveness and fostering student autonomy.